A novel blue emitting phosphor LaScO3:Bi3+ for white LEDs: high quantum efficiency, high color purity and excellent thermal stability. (December 2022) - Yang, H.; Li, P.; Fu, X.; Ye, Z.; Huo, X.; Wang, Y.; Wu, Q.; Suo, H.; Li, L.; Wang, Z.
Abstract: Series of blue phosphors La1- x Bi x ScO3 ( x = 0–0.6) (LSO) were synthesized by the high temperature solid state method. Under the 365 nm near ultraviolet (NUV) irradiation, when the value of x is increased, the phosphor can emit blue from deep to shallow. The LSO phosphor presents an internal quantum efficiency of up to 98%, high color purity of 92.26% as well as excellent thermal stability. When x  ≥ 0.2, Bi 3+ -doped phosphors have diverse FWHM ranging from 153 nm to 43 nm. Especially, when x  = 0.5, the material shows an abnormal thermal quenching, and emission intensity at 573K can reach 128.3% of that at room temperature. The white light emitting diode (LED) was fabricated by combining the NUV LED chip (370 nm) with a mixture of LSO:0.007Bi 3+ along with green Y3 (Al, Ga)5 O12 :Ce 3+ and red CaSiAlN3 : Eu 2+ phosphors, which show a high color rendering index Ra  = 90.2, a low correlated color temperature CCT = 3999 K. The results demonstrate that LSO phosphor has potential application in the field of white LEDs. Graphical abstract: Image 1 Highlights: LSO:Bi presents the high quantum efficiency of up to 98% and high color purity of 92.26%. When x  > 0.2, Bi 3+ -doped phosphor has diverse FWHM ranging from 153 nm to 43 nm. When x  = 0.5, the emission intensity at 573K can reach 128.3% of that at room temperature. White LEDs show Ra  = 90.2 and CCT = 3999 K.